A Clinico - Epidemiological Study of Traumatic Chest Injuries in a Rural Tertiary Care Centre in India: Our Experience (International Journal of Biomedical and Advance Research, 2015)
Introduction: Traumatic chest injuries are on the rise mainly due to increased frequency of road traffic accidents (RTAs) and rise in community disharmony. Chest injuries are one of the common causes of major mortality and morbidity. The management of traumatic chest injuries depends on the severity of injury, patient accessibility to nearby hospital and availability of resources at tertiary care Centre. Objectives: To analyze the Clinico - epidemiological pattern of traumatic chest injuries in our institution which is a rural tertiary care center. To recognize the common modes of traumatic chest injuries and their presentations to a tertiary care center. To assess the mode of management with the available facility. To assess the level of knowledge of the rural population about chest injuries and to create awareness among them regarding safe driving practice. Materials and Methods: It is a retrospective study of total 52 patients presenting to the emergency department with chest injuries of varying severity at SDUMC, Kolar from Jan 2013 to Dec 2013. Data collected regarding common injury modes, age and gender distribution, pre-hospitalization practices, clinical presentations, associated injuries, severity of injuries and management options from the hospital record section and these data were analyzed with descriptive statistics. Results: Chest trauma is most common in males in their thirties with mean age of presentation 39 years. The most common mode of injury was RTAs (67.3%) followed by fall from height (15.3%). Most of the pats were brought by patients attenders (46.1%). Most common presentation was chest pain and clinical sign was positive chest compression. Soft tissue injury to chest in the form of abrasions were most common injury type. About 21.1% of patients were presented with some form of pleural space collection, most common being combined Haemo-pneumothorax. Most of the patients treated symptomatically and in 10 patients (19.2%) Intercostal drain was placed. Conclusions: Chest injury are seen commonly in RTA patients. Most of the patients of chest injury had soft tissue trauma over chest in the form of abrasions and majority of these patients can be managed by symptomatic care and simple life saving intervention i.e., intercostal drainage. With increased RTAs it is needed to have public awareness regarding road safety measures and educating them about the first aid measures for trauma patients.